The Motivation of Fitness Center Members in Doing Fitness at NR Gym Fitness Center Medan (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
The type of research used in this study is to use quantitative methods of survey methods. Survey research deals with questions about one's own beliefs and behavior. In this study, the population was all Fitness Members at NR Gym Fitness Center Medan, which amounted to 3 people as the research sample, all of which were 3 people. The purpose of this research is to see the motivation of Fitness Center Members in doing fitness at NR Gym Fitness Center Medan. Respondents were asked to put a tick (√) in the available column according to the actual situation and this study used a Likert scale with a range of 5 (five). Based on the analysis found, it can be concluded that the Motivation of Fitness Center Members in Doing Fitness at NR Gym Fitness Center Medan is for fitness.